PERAN KEJAKSAAN DALAM TAHAP PENUNTUTAN TERHADAP ANAK YANG MELAKUKAN TINDAK PIDANA” (Studi Kasus Kejaksaaan Negeri Gorontalo) - Nopiana Mozin (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2019)
Public attorney is a governmental agency performing a state power of prosecution and its duties and responsibilities are regulated by Article 30 of Act No. 16 of 2004 about Attorney of Indonesian Republic. In this matter, a child who committed a crime, although qualitatively and quantitatively he or she might commit law breaking just like an adult, but he or she would not be handled like an adult. Attorney as an authoritative agency in prosecution is expected to make indictment that can give repent effect to the defendant and in the same time, it fulfill his or her rights. Problem statements of the research is to know what is profile of ordinance regulating position and role of public attorney in prosecution stage to a child who had committed a crime. Results of the research indicated that synchronous correlation between act and its application in Public Attorney of Gorontalo Regency. The Public Attorney performed its role according to the act.